Personalized tactics in cervical intraepithelial neoplasia of the cervix of varying severity - Tatyana Yu. Pestrikova; Ainur F. Ismaylova; Elena A. Yurasova; Oksana S. Tulvinskaya (IP Berlin A.V., 2022)
Purpose. To study the effectiveness of the drug diindolylmethane for the elimination of human papillomavirus (HPV) of high oncogenic risk in women with cervical intraepithelial neoplasia (CIN) of varying severity. Materials and methods. Conducted a comprehensive examination of 150 women, aged 20 to 49 years, with the presence of CIN. Verification of the diagnosis was carried out on the basis of data from clinical, cytological, colposcopic, and histological studies. HPV typing was carried out using the PCR (Kvant 21 test). Results. The obtained results emphasize the feasibility of using complex therapy for CIN of varying severity, including etiotropic correction of chronic cervicitis, with the parallel use of the drug diindolylmethane for 6 months, as well as destruction of the cervix in patients with CIN IIIII. The use of the drug diindolylmethane allows, with a statistical degree of certainty, to eliminate HPV of high oncogenic risk in patients with CIN of III. Conclusion. Despite the fact that we did not receive results indicating that it accelerates the elimination of HPV in patients with CIN III (p0.05), nevertheless, the use of diindolylmethane in patients with CIN III reduces the number of cases (p0.001) requiring expansion of surgical intervention (amputation of the cervix, extirpation of the uterus), which is important for patients of reproductive age.